КОРЕКЦІЯ ПОХИБОК ВИМІРЮВАЛЬНОГО КАНАЛУ СЕРЕДНЬОЇ АКТИВНОЇ ПОТУЖНОСТІ - Орнатський, Д.П.; Єгоров, С.В.; Довгань, В.В. (Інститут електродинаміки НАН України, Київ, 2022)
In the article is offered the structural scheme of error correction of the precision measuring channel of average active power for researches in laboratory conditions and exclusively within the limits of changes of the basic frequency of a network. A feature of the scheme is the use of calibration of functional transducers with piecewise linear approximation. The input voltages of these converters are a triangular voltage, which is formed at the output of the integrator by integrating rectangular bipolar meanders, which are formed from the output signals of the frequency divider phase shifter synchronized with the network by a device based on the original precision amplitude-pulse system of phase frequency tuning. Compensatory small-sized low-voltage transformers using measuring amplifiers with differentially split inputs are used as primary converters, which increases the linearity of the characteristic in a wide dynamic range, due to which additive-multiplicative correction of errors of the whole measuring path by two points is realized. The article presents the results of computer modeling of the main functional components of the measuring channel, which confirm its precision and high metrological characteristics. References 10, Figures 2.